2021
DOI: 10.1002/suco.202000628
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between internal viscous damping and stiffness of concrete material and structure

Abstract: This study focuses on the relationship between the internal viscous damping and the stiffness of concrete material and structure having small deformation amplitude. New damping parameters were proposed to describe the energy dissipation capacity and the vibration–amplitude attenuation rate. An improved damping suspension test method for predicting the essential material parameters, elasticity modulus and loss modulus, was developed and validated. The results show that the viscous damping energy dissipation cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Several studies have proposed that structural stiffness was strongly correlated with damping [ 49 ]. Previous research also confirmed a negative correlation between stiffness and internal viscous damping [ 50 ]. Thus, this paper selected stiffness as a mediation variable and investigated their dependencies accordingly.…”
Section: Resultssupporting
confidence: 66%
“…Several studies have proposed that structural stiffness was strongly correlated with damping [ 49 ]. Previous research also confirmed a negative correlation between stiffness and internal viscous damping [ 50 ]. Thus, this paper selected stiffness as a mediation variable and investigated their dependencies accordingly.…”
Section: Resultssupporting
confidence: 66%
“…The damping evaluation of concrete materials has been proposed by many researchers, Liang et al proposed a vibration amplitude attenuation coefficient 28 . In this study, the damping ratio calculation method was adopted from Clough et al 29 The definition of the damping ratio is shown in Equation (). ζsgoodbreak=ln()ym/yn2()ngoodbreak−mπ where y i is the amplitude at the i th cycle, therefore, the damping ratio could be calculated through the arbitrary two amplitude.…”
Section: Experiments Results and Analysismentioning
confidence: 99%
“…The damping evaluation of concrete materials has been proposed by many researchers, Liang et al proposed a vibration amplitude attenuation coefficient. 28 In this study, the damping ratio calculation method was adopted F I G U R E 1 0 The calculated impact time and impact force of different materials from Clough et al 29 The definition of the damping ratio is shown in Equation (5).…”
Section: Damping Ratiomentioning
confidence: 99%